Elderly onset of MELAS in a male: A case report - Diao, Sheng-Peng; Chen, Song-Fa; Liu, Ai-Qun; Zhou, Zhi-Hua; Peng, Zhong-Xing; Hong, Ming-Fan (Frontiers in Neurology, 2022)
Background Mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS) is one of the most common maternally inherited mitochondrial diseases which rarely affects elderly people. Case presentation We reported the case of a 61-year-old male patient with MELAS. He was experiencing acute migraine-like headaches as the first symptoms. Laboratory data showed elevated lactate and creatine kinase levels. Brain magnetic resonance imaging (MRI) found a high signal intensity lesion in the left occipital-temporal-parietal lobe on diffusion-weighted imaging (DWI). Magnetic resonance angiography (MRA) revealed reversible vasoconstriction of the middle cerebral arteries and superficial temporal arteries. A muscle biopsy suggested minor muscle damage. A genetic study revealed a mitochondrial DNA A3243G mutation. Conclusion Elderly onset of MELAS is rare and easily misdiagnosed as an ischemic stroke. MELAS with the onset of stroke-like episodes should be considered in adult or elderly patients with imaging findings that are atypical for cerebral infarction. The use of multimodal MRI in the clinical diagnosis of MELAS could be extremely beneficial.